2013
DOI: 10.1111/jcpe.12059
|View full text |Cite
|
Sign up to set email alerts
|

A review of the evidence for pathogenic mechanisms that may link periodontitis and diabetes

Abstract: Aims: To review the evidence for the molecular and cellular processes that may potentially link periodontal disease and diabetes. The pathogenic roles of cytokines and metabolic molecules (e.g. glucose, lipids) are explored and the role of periodontal bacteria is also addressed. Paradigms for bidirectional relationships between periodontitis and diabetes are discussed and opportunities for elaborating these models are considered. Methods: Database searches were performed using MeSH terms, keywords, and title w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
131
1
9

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(144 citation statements)
references
References 170 publications
3
131
1
9
Order By: Relevance
“…This does not come as a surprise since oral health is dependent on the metabolism and diet of the host, which in turn are dependent on the microbiome constitution and the health of the oral cavity. A recent study, examined the available metadata on the association of periodontal disease and diabetes and concluded that while there is substantial information on potential mechanistic pathways which support a close association between diabetes and periodontitis, there is still a real need for well controlled longitudinal clinical studies using larger patient groups, integrated with studies of in appropriate vivo models and cells/tissues in vitro [62]. From a clinical perspective, an example of the observed controversy is demonstrated by a few studies that have suggested a direct link between P. gingivalis ’ persistence in subgingival microbial biofilm and glycemic control in type 2 diabetes patients [62].…”
Section: Diabetes and Oral Microbesmentioning
confidence: 99%
See 1 more Smart Citation
“…This does not come as a surprise since oral health is dependent on the metabolism and diet of the host, which in turn are dependent on the microbiome constitution and the health of the oral cavity. A recent study, examined the available metadata on the association of periodontal disease and diabetes and concluded that while there is substantial information on potential mechanistic pathways which support a close association between diabetes and periodontitis, there is still a real need for well controlled longitudinal clinical studies using larger patient groups, integrated with studies of in appropriate vivo models and cells/tissues in vitro [62]. From a clinical perspective, an example of the observed controversy is demonstrated by a few studies that have suggested a direct link between P. gingivalis ’ persistence in subgingival microbial biofilm and glycemic control in type 2 diabetes patients [62].…”
Section: Diabetes and Oral Microbesmentioning
confidence: 99%
“…A recent study, examined the available metadata on the association of periodontal disease and diabetes and concluded that while there is substantial information on potential mechanistic pathways which support a close association between diabetes and periodontitis, there is still a real need for well controlled longitudinal clinical studies using larger patient groups, integrated with studies of in appropriate vivo models and cells/tissues in vitro [62]. From a clinical perspective, an example of the observed controversy is demonstrated by a few studies that have suggested a direct link between P. gingivalis ’ persistence in subgingival microbial biofilm and glycemic control in type 2 diabetes patients [62]. In contrast a recent in vivo mice study has shown no alteration of onset or severity of type 2 diabetes by P. gingivalis -induced periodontitis [63].…”
Section: Diabetes and Oral Microbesmentioning
confidence: 99%
“…However, the main limitation with this approach is that the complex interplay between PD and T2D can make it difficult to distinguish whether any observed differences in subgingival bacterial profiles are due to PD status or the result of diabetic state (Taylor et al, 2013). On the other hand, the main advantage of using animal models is that selected aspects of a complex interaction between diseases may be studied in a controlled manner.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in the Oral Infections, Glucose Intolerance, and Insulin Resistance Study, increasing colonization levels of periodontal pathogens were observed with increasing prevalence of prediabetes (Demmer et al, 2015). However, other studies have been not demonstrated such changes of the microbiota (Taylor, Preshaw, & Lalla, 2013). …”
Section: Introductionmentioning
confidence: 90%
“…In individuals susceptible to periodontitis, absence of resolution of periodontal inflammation results in chronic inflammation, which may have a systemic impact (D'Aiuto et al, 2013;Dietrich et al, 2013;Ide and Papapanou, 2013;Linden and Herzberg, 2013;Taylor et al, 2013). The acute inflammatory response is protective, but failure to remove the inflammatory cells, especially neutrophils, promotes chronic, pathological and destructive lesions.…”
Section: Discussionmentioning
confidence: 99%